Análisis, diseño e implementación de la tecnología Voip para la concesión minera paríso de la compañía Corporación Minera Rey de Oro Cormirey S.A. durante el período 2012 - 2013 - Valdivieso Espinoza, Diego José (2013)
The development of this thesis project is based on the analysis, design and implementation of VoIP for granting Mining Corporation Paradise King Gold Mining Company SA which does not have a network that allows you to join with other agencies Business Group production units Machuca, research has been conducted as interviews and surveys pair used to determine the problems that currently exist in the organization.